THE LESSONS FROM THE EURO EXPERIENCE - Griffiths, Richard (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Twenty years ago, amid a great fanfare of enthusiasm, the Treaty of Maastricht created the European union and inaugurated the process for creating a single European currency for most of the then members (except the UK and Sweden, and later Denmark, that were given a temporary exemption) and all future members. Twenty years later, the anniversary of the treaty passed almost unnoticed (European Policy Centre, 2012). On that day, however, the impact of the treaty was never far from the headlines, as had also been the case for almost every day over the previous months. The Lehman brothers bankruptcy in September 2008 not only triggered a financial crisis that threatened to engulf the world, but it set in motion a series of shocks that have since reverberated through the Euro-area. It is fair to say that the crisis-management has not been an example of stream-lined efficiency, and there are lessons to be learned from that experience. However, the development of the Euro, and the crisis that has subsequently engulfed it, holds lessons in another direction. The European Union has long been held as a model, or an inspiration, for other experiments in regional cooperation and integration, including Mercosul, ASEAN and SADC. The model embodied an sequence of steps leading to ‘ever closer union’ that moved from a free trade area through a customs union and a single market and culminated in economic and monetary union. With the signing and implementation of the Treaty of Maastricht, the European Union had embarked on the penultimate step in this progression. But only half of it – a monetary union without a fiscal union. The Euro-crisis has now called that achievement into question and, in the process, undermined the authority of those espousing a European route towards closer integration, both for themselves as well as for other nations. As a convinced federalist, myself, I would not recommend abandoning the European example altogether, but if there is a lesson to be learned from this sorry episode, it is this: “if you are going to do it, do not do it this way”. This article examines the European experience with economic and monetary union from three perspectives – the design, the implementation and the management of the euro – before exploring the implications of the current crisis.